Implementasi Green Bond dalam Sektor Investasi Infrastruktur di Indonesia Guna Mewujudkan Sustainable Economic Development - Jumantoro, Tegar Raffi Putra; Novemyanto, Alfin Dwi (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Indonesia faces significant challenges in achieving sustainable development, particularly due to the negative environmental impacts of rapid economic growth, such as deforestation, air and water pollution, and the increase in greenhouse gas emissions. Green Bonds have great potential as a financial instrument to promote sustainable development in Indonesia. Indonesia is actively working to develop the market through key policies such as the Financial Services Authority Regulation (POJK) No. 51/POJK.03/2017, which regulates the issuance and offering of sustainable bonds, thus enhancing the suitability of green bonds to finance environmentally friendly projects. The research method used in this study is a normative legal approach with a focus on laws and regulations (UU) and a library research method. Through this approach, the study analyzes relevant regulations and existing literature to explore the potential and challenges Indonesia faces in implementing green bonds, particularly in the infrastructure investment sector. The implementation of green bond investments in Indonesia, especially in the infrastructure sector, is a strategic step in line with efforts to achieve sustainable development. To achieve this, Indonesia must also consider integrating green bonds into broader development policies. This includes developing strategies that combine economic, social, and environmental aspects in the planning and implementation of infrastructure projects.